Magnetic susceptibility controlled by climate-driven weathering intensity - Aubineau Jérémie; Antonio Paul Y.J.; El Bamiki Radouan; Parat Fleurice; Camps Pierre; Raji Otmane; Jourani Es-Said; Bodinier Jean-Louis; Macouin Mélina; Gilder Stuart; Rousse Sonia; Séranne Michel (BSGF - Earth Sciences Bulletin)
Magnetic susceptibility (MS) variations are commonly attributed to eustatic and/or climatic changes that impact the delivery of fine-grained detrital magnetic minerals. However, the mechanism responsible for sourcing magnetic minerals from land to the ocean is not fully understood. Bulk mineralogy, Rietveld refinements of powder XRD patterns, and whole-rock geochemistry, combined with a MS investigation across a ∼290 m-thick Upper Cretaceous/Paleogene sedimentary sequence at Erguita, Morocco, imply that iron is exclusively detrital in origin. Moreover, MS fluctuations occurred independently from depositional setting and sea-level variations. Rock magnetism investigations further show that a complex assemblage of ferromagnetic sensu lato minerals is recorded in the Erguita sedimentary section, and a proportion of more or less oxidized magnetite supplied to the depositional setting controls the MS variations. This study chronicles that the weathering of the Anti-Atlas crystalline basement led to the supply of detrital Fe-bearing phyllosilicates and ferromagnetic (sensu lato) Fe-oxides to the eastern passive margin of the Atlantic Ocean from the Late Cretaceous to the mid-Paleogene. Higher weathering intensity drove up the detrital magnetic material in all lithologies, which, in turn, increased the MS signal. Importantly, this model nicely coincides with the climatic upheavals of the Paleogene. We propose that this unrecognized link between MS and climate-driven weathering intensity is paramount to unraveling the origin of the low MS interval below the Cretaceous-Paleogene boundary. Climate cooling resulting in reduced weathering rather than a global acidification triggered by Phase 2 of Deccan volcanism could help explain the MS trend at that time.